Phase separation and long-wavelength charge instabilities in spin-orbit coupled systems. (21st January 2015) - Seibold, G.; Bucheli, D.; Caprara, S.; Grilli, M.
Abstract: We investigate a two-dimensional electron model with Rashba spin-orbit interaction where the coupling constant depends on the electronic density. It is shown that this dependence may drive the system unstable towards a long-wavelength charge density wave (CDW) where the associated second-order instability occurs in close vicinity to global phase separation. For very low electron densities the CDW instability is nesting-induced and the modulation follows the Fermi momentum k F . At higher density the instability criterion becomes independent of k F and the system may become unstable in a broad momentum range. Finally, upon filling the upper spin-orbit split band, finite momentum instabilities disappear in favor of phase separation alone. We discuss our results with regard to the inhomogeneous phases observed at the LaAlO3 /SrTiO3 or LaTiO3 /SrTiO3 interfaces.